Proposals and Analysis of the Effects of Acoustic Corrections in a Modern Church. Issue 3 (December 2015) - Gagliano, Antonio; Nocera, Francesco; Cicero, Andrea; Gioia, Mirko Cascio
It is rather common experience to observe that many contemporary churches, in contrast with the effort to achieve refined architectonic shapes and finishes, exhibit poor acoustic quality, such as high reverberation times and low speech intelligibility. The causes of such deficiencies are ordinarily generated by the smooth and hard surfaces of walls, floor and ceiling that focus most of sound energy in late reflections, diminishing the effectiveness of direct and early reflected sound. Recently, the authors have been involved for analyzing the acoustic behavior of a modern church situated in Ragusa, (Italy), with the aim to individuate suitable interventions for improving the acoustic quality of that church. Preliminarily, a measurement survey was conducted to evaluate the main acoustic indices proposed by ISO 3382 (T30, STI, EDT, C80, D50 ) and portray the current acoustic climate. After that, the Authors developed a simulation on a 3D model of the church, in order to calibrate the model comparing measured and simulated acoustic parameters. The previously described activities are necessary for testing the reliability and accuracy of the prediction of the acoustic simulations. The subsequent step of the work consists in the choice of suitable interventions for the acoustic corrections; three different typologies of materials were evaluated. Globally, the acoustic corrections allow to obtain noteworthy improvements of the acoustic quality of the church, e.g. the T30 decrease from 7.3 to 2.5 s and the STI increase from 33% to 40%, at 1000 Hz. Further, the influence of the variation of the audience presence was analyzed, finding out a strict correlation between occupancy percentage and the law of variation of T30 . Finally, after the realizations of one of the suggested interventions of acoustic corrections, the Authors conducted a second survey to evaluate the effects of the refurbishment interventions on the acoustic climate. Since the obtained results do not match very well with the design previsions, some hypotheses that can justify such discrepancy are illustrated.